2017
DOI: 10.1097/wnr.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Cochleovestibular gene transfer in neonatal mice by canalostomy

Abstract: Impairments of the inner ear result in sensorineural hearing loss and vestibular dysfunction in humans. A large proportion of these disorders are congenital, and involve both auditory and vestibular systems. Therefore, genetic interventions to correct deficits must be administered during early developmental stages. In this study, we evaluated inner ear gene transfer in neonatal mice by canalostomy using an adeno-associated virus serotype 8 (AAV8) vector. AAV8 with the green fluorescence protein (GFP) gene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…To evaluate the safety and efficiency of canalostomy for inner ear gene delivery, AAV8-GFP was injected into the inner ear of adult and neonatal mice. All animals exhibited normal ABR thresholds and swimming test scores after AAV8-GFP injection 18,30 . Immunohistology revealed that, in the auditory sensory epithelium, inner hair cells (IHCs) and a few outer hair cells (OHCs) of the basal turn showed robust GFP expression .…”
Section: Representative Resultsmentioning
confidence: 96%
“…To evaluate the safety and efficiency of canalostomy for inner ear gene delivery, AAV8-GFP was injected into the inner ear of adult and neonatal mice. All animals exhibited normal ABR thresholds and swimming test scores after AAV8-GFP injection 18,30 . Immunohistology revealed that, in the auditory sensory epithelium, inner hair cells (IHCs) and a few outer hair cells (OHCs) of the basal turn showed robust GFP expression .…”
Section: Representative Resultsmentioning
confidence: 96%
“…One limitation of this study was that it focused solely on the utilization of AAV2/Anc80L65; other serotypes were not screened. Of note, in neonatal mice injected with AAV8 via a PSCC canalostomy, transduction of IHCs was 69–76% 18 , suggesting that transduction efficiency with this approach may be serotype dependent. Additionally, one technical difficulty of the PSCC canalostomy injection is that it is impossible to determine whether the viral suspension is administered into the endolymphatic or perilymphatic space of PSCC 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that direct injection of adenovirus via the semicircular canal in mice led to transduction, predominantly in the vestibular organ (Kawamoto et al, 2001). Other mouse studies demonstrated that viral vectors injected from the semicircular canal diffuse into the cochlea, introducing transgene expression in cochlear hair cells (Pfannenstiel et al, 2009; Guo et al, 2017). Therefore, further studies are required to evaluate the efficiency of injection from the semicircular canal and diffusion of the injected solution into the inner ear canal in the common marmoset.…”
Section: Discussionmentioning
confidence: 99%